Communicative tensions of meaningful work: The case of sustainability practitioners. (May 2017) - Mitra, Rahul; Buzzanell, Patrice M
This study, based on in-depth interviews with 45 practitioners in the emerging field of environmental sustainability, argues for a more nuanced approach to studying the meaningfulness of work. Drawing from the tension-centered approach, we posit that sustainability practitioners derived meaningfulness in tensional ways from circumstances and factors that were both enabling and constraining, stemming from various organizational, professional and political structures. This occurs through ongoing negotiation that spans everyday work processes, the perceived impact of such work, and participants' career positioning. In addition to examining meaningfulness as a dynamic and contested negotiation, rather than a purely positive outcome, the political implications of such meaning-making are traced. We close by discussing some implications for future research on meaningfulness of work.